PATRIARCH YOSYP SLIPYY IN THE CONTEXT OF MUSICAL CULTURE OF UKRAINIAN DIASPORA - Karas, G. V. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2020)
The article is dedicated to the elucidation of archbishop of Ukrainian Greek-Catholic Church Yosyp Slipyy activity in the context of reserving and development of musical culture of Ukrainian Diaspora. Many-sided activity of the Head of church is distinguished namely: his visits of different world countries, participation in reforming of church singing and celebrations, development of spiritual education, contacts with musical cultural workers.